1973
DOI: 10.1172/jci107195
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture Studies of Sodium Tranport in the Remnant Kidney of the Dog THE EFFECT OF GRADED VOLUME EXPANSION

Abstract: A B S T R A C T Proximal and distal tubule micropuncture studies were performed to examine the response to graded extracellular volume (ECV) expansion in 10 normal dogs (stage I), 11 dogs with a unilateral remnant kidney (stage II), and 7 dogs with a remnant kidney after removal of the contralateral kidney (stage III). Before ECV expansion in stage III, there was a suggestive reduction in proximal tubule as well as loop fractional reabsorption of sodium. After ECV expansion to 3% body weight proximal tubule re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…This was carried out by infusion of calcium chloride in saline-loaded normal dogs or administration of highly purified parathyroid hormone to saline-loaded TPTX dogs. Saline-loaded animals were used because it has been shown that proximal tubule FR sodium in the dog, once suppressed by saline infusion, tends to remain unaffected by further inhibitory maneuvers such as graded volume expansion (56,57). Indeed, neither calcium infusion nor parathyroid hormone administration, both of which have been shown to reduce proximal tubule sodium reabsorption (12,18,58), significantly altered proximal TF/P inulin in the saline-loaded animals in the present studies.…”
Section: Discussionmentioning
confidence: 74%
“…This was carried out by infusion of calcium chloride in saline-loaded normal dogs or administration of highly purified parathyroid hormone to saline-loaded TPTX dogs. Saline-loaded animals were used because it has been shown that proximal tubule FR sodium in the dog, once suppressed by saline infusion, tends to remain unaffected by further inhibitory maneuvers such as graded volume expansion (56,57). Indeed, neither calcium infusion nor parathyroid hormone administration, both of which have been shown to reduce proximal tubule sodium reabsorption (12,18,58), significantly altered proximal TF/P inulin in the saline-loaded animals in the present studies.…”
Section: Discussionmentioning
confidence: 74%
“…In chronic renal disease, the excretion of sodium by the kidney is known to change during the course of the disease process [1][2][3]. A number of factors have been evoked to explain this adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in fractional water excretion in these animals may not be influenced by plasma ANF levels. Increases in fractional excretion of water in renal failure animals were reported before [25,26], This could be due to changes in intrarenal blood flow and inability to respond to vasopres sin. Preliminary studies in 5/6 nephrectomized rats showed that cyclic AMP generation by inner medullary collecting duct cells in response to vasopressin was impaired [27].…”
Section: Discussionmentioning
confidence: 79%